PENGARUH EKSPOR DAN IMPOR BUAH-BUAHAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2011-2018 - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to examine the effect of fruit exports, Chinese inflation, fruit imports and Chinese population on economic growth in Indonesia in 2011-2018. The data used in this study are secondary time series data. Data analysis method is to use multiple linear regression equation tests with the help of the SPSS program. The results showed that; Fruit exports, Chinese inflation, and fruit imports partially have a significant effect on Indonesia's economic growth in 2011-2018. The Chinese population partially have not significantly influence Indonesia's economic growth in 2011-2018. Fruit exports, Chinese inflation, fruit imports and Chinese population simultaneously have a significant effect on Indonesia's economic growth in 2011-2018. Fruit exports, Chinese inflation, fruit imports and Chinese population have the ability to explain its effect on Indonesia's economic growth in 2011-2018 of 91%. The remaining 9% is influenced by other variables outside this research model.